Assessing Signalized Intersections During Rush Hours Through Geometric Planning and Road Widening Intersection - Salman - Salman; Darmawan Pontan; Noer Fadly; Veby Irawandi; Endah Kurniyaningrum; Tulus Widiarso (Teras Jurnal : Jurnal Teknik Sipil, 2025)
Abstract   As consumers and businesses rely on the efficiency, safety, and reliability of transportation networks, the quality of urban life is at risk due to increasing traffic congestion. The current study aims to evaluate the capacity of an intersection by recalculating the existing condition and making changes with geometric improvements, namely symmetrizing the intersection arms and traffic separation islands and widening the intersection arms. Factors that affect traffic congestion at intersections in the Banda Aceh area, such as driver behavior, traffic light capacity, peak-hour drivers, and intersection design. This study compares on-site data with the performance of signalized intersections using various traffic methodologies. With a population of 261,000 in Banda Aceh, Simpang Surabaya is known as a busy route in urban life. Two techniques are used for the analysis: applying the Indonesian Highway Capacity Manual (MJKI) to the road widening and geometric re-planning. The results show that the intersection capacity is close to saturation, with a saturation value of 1.336 which exceeds 0.85 due to asymmetric traffic islands, high volumes, and long cycle times. Geometric changes and wider intersection roads reduce this value to 0.83. The results indicate that Simpang Surabaya (the intersection of Surabaya) needs to be widened immediately and properly. Further research is recommended to evaluate other intersections in the city of Aceh with quite busy traffic density to carry out calculations and handling by using different of MJKI accordingly.   Keywords: Traffic volume; signalized intersection, capacity; degree of saturation; traffic delay   Abstrak   Ketika konsumen dan perusahaan bergantung pada efisiensi, keamanan, dan keandalan jaringan transportasi, kualitas kehidupan perkotaan berada dalam risiko akibat meningkatnya kemacetan lalu lintas. Penelitian saat ini bertujuan untuk mengevaluasi kapasitas persimpangan dengan menghitung ulang kondisi eksisting dan melakukan perubahan dengan perbaikan geometrik yaitu mensimetriskan lengan-lengan simpang dan pulau pemisah arus lalu lintas dan pelebaran lengan simpang. Faktor -faktor yang mempengaruhi kemacetan lalu lintas di persimpangan jalan di daerah Banda Aceh, seperti perilaku pengemudi, kapasitas lampu lalu lintas, pengemudi pada jam sibuk, dan desain persimpangan. Studi ini membandingkan data di lokasi dengan kinerja persimpangan yang dilengkapi sinyal menggunakan berbagai metodologi lalu lintas. Dengan 261.000 penduduk, Simpang Surabaya di Banda Aceh dikenal sebagai jalur sibuk dalam kehidupan perkotaan. Dua teknik digunakan untuk analisis: menerapkan manual kapasitas jalan raya Indonesia (MJKI) pada pelebaran jalan dan perencanaan geometrik ulang. Hasilnya menunjukkan bahwa kapasitas persimpangan mendekati jenuh, dengan nilai jenuh sebesar 1,336 yang melebihi 0,85 akibat pulau lalu lintas yang asimetris, volume tinggi, dan waktu siklus yang panjang. Perubahan geometris dan jalan persimpangan yang lebih lebar mengurangi nilai ini menjadi 0,83. Hasilnya menunjukkan bahwa Simpang Surabaya perlu segera diperlebar dengan baik. Penelitian selanjutnya dianjurkan mengevaluasi simpang dengan kepadatan yang cukup sibuk di daerah Aceh lainnya untuk dilakukan kalkulasi dan penanganan secepatnya.   Kata kunci: Volume lalulintas, simpang bersinyal, kapasitas, derajat kejenuhan, tundaan lalu   lintas